Analyse des conditions de travail des travailleurs intérimaires - Rachid Belkacem; Laurence Montcharmont (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper analyzes the main characteristics of the working conditions of temporary workers in France. It examines the data from a large study conducted in 2008/2009 and financed by the Regional Labor Department of Lorraine (DRTEFP- Lorraine). Our research was organized around two surveys involving temporary workers in industry and/or construction and civil engineering. This article shows that temporary employees’ vulnerability to occupational accidents is higher than that of companies’ permanent employees. This vulnerability can be explained by relatively more difficult working conditions. Quite often, these workers must quickly adapt to different and evolving work contexts.